ANALYSIS OF GOLD PAWN PROMOTION STRATEGY AT PT BANK ACEH SYARIAH KUALA SIMPANG - Irwanto; Iswandi Idris; Juwita Adelia Ningsih (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the types of gold pawn promotion strategies and evaluate the implementation of gold pawn strategies related to advertising, personal selling, sales promotion, and public relations at PT. Bank Aceh Syariah, Kuala Simpang Branch. and what are the obstacles in implementing these strategies. The results of this study indicate that the strategy is quite good, but there are still obstacles, namely the lack of human resources in the gold pawn section. Therefore, promotions in the public relations and direct sales sections cannot be carried out. However, for now, the strategy implemented has been very effective, seen from the increase in customers and revenue every year.